Effects of Mediterranean Diet in Patients with Nonalcoholic Fatty Liver Disease: A Systematic Review, Meta-Analysis, and Meta-Regression Analysis of Randomized Controlled Trials - Kawaguchi, Takumi; Charlton, Michael; Kawaguchi, Atsushi; Yamamura, Sakura; Nakano, Dan; Tsutsumi, Tsubasa; Zafer, Maryam; Torimura, Takuji (Seminars in Liver Disease, 2021)
We conducted a meta-analysis to investigate the effects of the Mediterranean Diet (Med-Diet) on hepatic steatosis and insulin resistance in patients with nonalcoholic fatty liver disease (NAFLD). Six randomized controlled trials were selected for the meta-analysis (sample size: 250 participants). In the meta-analysis, there was no significant difference in body mass index and waist circumference between the Med-Diet and control groups. Med-Diet significantly reduced fatty liver index (FLI) compared with the control diet (standard mean difference [SMD]: –1.06; 95% CI: –1.95 to –0.17; p = 0.02). Med-Diet significantly reduced homeostasis model assessment of insulin resistance (HOMA-IR) compared with the control diet (SMD: –0.34; 95% CI: –0.65 to –0.03; p = 0.03). Similarly, a meta-regression analysis using age showed that Med-Diet significantly reduced FLI and HOMA-IR (95% CI: –0.956 to –0.237, p = 0.001 and 95% CI: –0.713 to –0.003, p = 0.048, respectively). This meta-analysis demonstrated that Med-Diet improved hepatic steatosis and insulin resistance in patients with NAFLD. Thus, Med-Diet is a beneficial pharmaconutritional therapy in patients with NAFLD.
Keywords: Mediterranean diet; nonalcoholic fatty liver disease; metabolism; lipid metabolism; insulin resistance; liver stiffness